Auditory verbal hallucinations result from combinatoric associations of multiple neural events - Stephane, Massoud (Frontiers in Human Neuroscience, 2013)
While Auditory Verbal Hallucinations (AVH) refer to specific experiences shared by all subjects who have AVH- the perception of auditory speech without corresponding external stimuli, the characteristics of these experiences differ from one subject to another. These characteristics include aspects such as the location of AVH (inside or outside the head), the linguistic complexity of AVH (hearing words, sentences, or conversations), the range of content of AVH (repetitive or systematized content), and many other variables. In another word, AVH are phenomenologically heterogeneous experiences. After decades of research focused on a few explanatory mechanisms for AVH, it is apparent that none of these mechanisms alone explains the wide phenomenological range of AVH experiences. To date, our phenomenological understanding of AVH remains largely disjointed from our understanding of the mechanisms of AVH. For a cohesive understanding of AVH, I review the phenomenology and the cognitive and neural basis of AVH. This review indicates that the phenomenology of AVH is not a pointless curiosity. How a subject describes his AVH experiences could inform about the neural events that resulted in AVH. I suggest that a subject-specific combinatoric associations of different neural events result in AVH experiences phenomenologically diverse across subjects.